Well-being at work on farms in Finland : stress, safety in animal handling and working conditions of women on dairy farms - Kallioniemi, Marja (MTT, 2013)
The restructuring of agriculture in Finland has resulted in several types of change on farms during recent years. The field areas and sizes of herds per farm have been increasing, while the number of farms has been decreasing. Concurrently, the risks of agriculture have increased. Ongoing change has been described as a modernization process from traditional farming towards a more enterprise form of agriculture. Farms are mainly owned by private persons in Finland. The farm entrepreneurs and their well-being at work are at the core of this thesis. Human capacity, including work ability, health and coping has been assessed as a crucial element for the success of the farm enterprise. Stress is commonly described as a situation in which the demands of work are greater than the worker is able to cope with. This type of conflicting and strenuous situation may induce different kinds of symptoms and diseases in people. Agriculture is among the most injury-prone working sectors. The aims of this research were to determine the prevalence and symptoms of stress among full-time farm entrepreneurs, identify possibilities to increase occupational safety during animal handling work and characterise the negative and positive elements of women’s working conditions on dairy farms. These aims were addressed through two main samples. The first was a telephone survey of 1 182 full-time farmers focusing on stress and symptoms among the respondents. Secondly, a qualitative study was carried out involving ten female farmers working on dairy farms that focused on occupational safety during animal handling and the working conditions of women. According to the results, full-time farmers experienced less stress than among the general working population in Finland. One in four (26%) full-time farmers had symptoms of weakness or fatigue and one in five (19%) farmers had symptoms of insomnia or difficulties in falling asleep. Both of these symptoms had increased statistically significantly when compared to an earlier follow-up survey in 1992. Problems with social relationships and lowered state of health were associated with stress and symptoms. Pesticide usage of over two weeks during the previous growing period had an association with symptoms. Based on the literature review, the most common stressors among farm entrepreneurs were the farm economy, regulations, the weather, dangers in farm work and new legislation. In the qualitative study occupational accidents were frequent: nearly all women had suffered one or more injuries during the previous two years. Unexpected animal behavior was considered as the most significant injury risk. The results revealed that a positive relationship between the stockperson and cattle as well as knowledge of animal behaviour and welfare enabled a safer working environment to gradually be built in the cattle barn. In practice, the stockperson should keep physical conditions animal friendly, perform positive and predictable routines, habituate young calves to people, avoid the separation of an individual animal, not dominate animals by force and be patient during work among farm animals. In addition, it is important to always be prepared for self-defence. Female respondents were involved in wide range of different work tasks on dairy farms. As a positive element, nearly all respondents considered work with animals and close to nature to be rewarding. On the other side, women’s working days were long. Old traditions may create invisible barriers to organizing the work in a more functional way on enlarged farm units. Most women chose farm entrepreneur as their professional title, but their professional position was often undefined or misunderstood. The valuable contribution of female farm entrepreneurs to agriculture should be recognized and supported, because women’s expertise within agriculture is important in finding solutions for future challenges such as sustainable, organic agriculture and animal welfare. Due to the ongoing restructuring of the agricultural sector in Finland, the well-being at work among farm entrepreneurs requires support, efforts and attention. The working environment related to agriculture includes several risks such as stress, injury and an impairment of work ability.

Viime vuosina maatalouden rakennemuutos on vaikuttanut suomalaiseen maatalouteen monin tavoin. Peltoala ja tuotantoeläinten määrä tilaa kohti ovat kasvaneet, kun taas tilojen lukumäärä on vähentynyt. Samanaikaisesti maatalouden riskit ovat kasvaneet. Meneillään olevaa muutosta on kuvailtu prosessiksi, jossa siirrytään perinteisestä maataloudesta uudentyyppiseen, yritysmäisempään maatalouteen. Suomessa maatilat ovat pääosin yksityishenkilöiden omistuksessa. Väitöskirjan keskiössä ovat maatalousyrittäjät ja heidän työhyvinvointinsa. Inhimillinen toimintakyky, johon vaikuttavat terveydentila, työkyky ja hyvinvointi, on keskeinen, maatilayrityksen menestykseen vaikuttava tekijä. Stressiä kuvaillaan yleensä tilanteena, jossa työn tekijälleen asettamat vaatimukset ovat suuremmat kuin mistä ihminen kykenee selviytymään. Tällainen ristiriitainen ja kuormittava tilanne voi aikaansaada erilaisia oireita ja sairauksia. Maatalous on yksi tapaturma-altteimmista työaloista. Tutkimuksen tavoitteina oli määrittää stressin esiintymistä ja oireita päätoimisilla maatalousyrittäjillä, etsiä keinoja parantaa työturvallisuutta eläintenhoitotyössä sekä selvittää naisten työolosuhteiden myönteisiä ja kielteisiä piirteitä maidontuotantotiloilla. Tavoitteisiin paneuduttiin kahden tutkimusaineiston avulla. Stressiä ja sen oireita tutkittiin puhelinhaastatteluaineiston avulla, johon vastasi 1 182 päätoimista viljelijää. Toiseen, laadulliseen tutkimukseen osallistui kymmenen maidontuotantotiloilla työskentelevää naista. Jälkimmäinen tutkimus paneutui työturvallisuuteen eläinten hoitotyössä ja naisten työolosuhteisiin. Kyselytutkimuksen tulosten mukaan päätoimiset maatalousyrittäjät kokivat vähemmän stressiä kuin työikäinen väestö Suomessa keskimäärin. Noin joka neljäs (26 %) päätoiminen maatalousyrittäjä koki voimattomuutta ja väsymystä ja noin joka viides (19 %) koki unettomuutta tai vaikeuksia nukahtaa. Nämä molemmat oireet olivat lisääntyneet tilastollisesti merkitsevästi edelliseen, vuoden 1992 seurantatutkimukseen verrattuna. Ongelmat sosiaalisissa suhteissa ja heikentynyt terveydentila olivat yhteydessä stressiin ja henkiseen hyvinvointiin liittyvien oireiden kokemiseen. Myös yli kahden viikon pituinen torjunta-aineiden käyttö edellisen kasvukauden aikana oli yhteydessä oireiden kokemiseen. Kirjallisuuskatsauksen mukaan maatilayrittäjille aiheuttavat stressiä tilan taloudellinen tilanne, säännöt, sää, maatilalla työskentelyyn liittyvät vaarat ja uusi lainsäädäntö. Laadullisessa tutkimuksessa havaittiin, että työtapaturmat olivat yleisiä: miltei kaikki naiset olivat kokeneet yhden tai useamman tapaturman kuluneiden kahden vuoden aikana. Eläinten odottamaton käyttäytyminen arvioitiin merkittävimmäksi tapaturmariskiä lisääväksi tekijäksi. Tulokset osoittivat, että navetan työturvallisuutta on mahdollista vähitellen parantaa, kun luodaan myönteinen vuorovaikutussuhde hoitajan ja eläinten välille sekä lisätään eläinten hyvinvointiin ja käyttäytymiseen liittyvää tietämystä. Käytännössä eläimille tarjotaan eläinystävälliset hoito-olosuhteet, toteutetaan ennustettavia ja lempeitä rutiineja, totutetaan vasikoita ihmisiin ja vältetään yhden eläinyksilön erottamista muista eläimistä. Eläimiä ei saa hallita pelon avulla, ja hoitotöiden aikana käyttäydytään kärsivällisesti. Hyökkäävän eläimen varalta tulisi olla aina varautunut puolustautumaan. Naiset tekivät maitotiloilla monia erilaisia työtehtäviä. Miltei kaikki naiset pitivät luonnonläheistä työtään eläinten parissa palkitsevana, mutta työpäivät olivat pitkiä. Vanhat perinteet voivat luoda näkymättömiä raja-aitoja, jos tavoitteena on järjestää työ aiempaa toimivammalla tavalla laajentaneella maatilalla. Suurin osa naisista halusi olla ammattinimikkeeltään maatalousyrittäjä, mutta heidän ammatillinen asemansa oli usein määrittelemätön tai väärin ymmärretty. Naisten arvokas työpanos maatalouteen ei saisi jäädä unohduksiin tai ilman tukea. Naisten ammattitaitoa ja osaamista maataloudessa tarvitaan, kun etsitään ratkaisuja tulevaisuuden haasteisiin eli kestävään maatalouteen, luomutuotantoon sekä eläinten hyvinvoinnin edistämiseen. Meneillään olevan maatalouden rakennemuutoksen takia maatalousyrittäjien työhyvinvointi tarvitsee tukea. Maatalouden työympäristö sisältää useita riskitekijöitä kuten stressiä, tapaturmavaaroja ja puutteellisesta työkyvystä aiheutuvia hankaluuksia.
Keywords: Maatalous - yleistä, maatalousekonomia,maatalousneuvonta, maaseudun kehittäminen; työolosuhteet; well-being at work; työturvallisuus; lypsykarjatilat; naiset; stressi; turvallisuus; maatalous; agriculture; stress; symptoms; safety at work; females; women; women farmers; working conditions; dairy farms; työhyvinvointi; oireet; työolot